Beauty proportions in Thai art, Busabok style - Chantharamporn, Arnuphap (DEC Journal : Art and Design, 2023)
Style Busabok Architecture is an art created as a response to the use of Buddhism, rituals, and the monarchy; that is, as a form of preaching. Therefore, creation, invention, design, and decoration produce significance and sacredness. In design and creativity, there are tenets and concepts that we comprehend. The context of Busabok art and its relation to the utilization of space are both for use in proclaiming Dharma and positioning elements in the sermon pavilion area. From a compilation of comparative studies in numerous fields, it was determined that the approach to creating aesthetics in areas that required excellent usability and reflected the beliefs of Buddhism was derived from the design principles-based guidelines. The grandeur of Thai Dhamma arts is known and acknowledged by us. However, we are unaware of the beauty's origin or purpose. Therefore, the study employed the decoding procedure as an artistic subject to demonstrate all design and creative approaches. The pulpit was used as a comparative example of a small architectural structure in the study of the traditional Thai form of Busabok art. It is believed, based on the observations in the hypothesis, that there exists a distinct system or theory for determining the ideal proportions of beauty. In the design and creation of traditional Thai Busabok-style pulpit art, it is possible to identify or compare certain geometric proportions. As a result of the study, there were discoveries in explaining the proportion of beauty in Busabok art that does not rely on the individual preferences of the artist. But it comes from designing and adjusting the proportions to find the perfect use for the intended purpose and can also be used to explain and define the use of proportion theory in Thai art as well.